Upstairs Market for Principal and Agency Trades: Analysis of Adverse Information and Price Effects - Smith, Brian F.; Turnbull, D. Alasdair S.; White, Robert W. (Journal of Finance, 2001)
ABSTRACT This paper directly tests the hypothesis that upstairs intermediation lowers adverse selection cost. We find upstairs market makers effectively screen out information‐motivated orders and execute large liquidity‐motivated orders at a lower cost than the downstairs market. Upstairs markets do not cannibalize or free ride off the downstairs market. In one‐quarter of the trades, the upstairs market offers price improvement over the limit orders available in the consolidated limit order book. Trades are more likely to be executed upstairs at times when liquidity is lower in the downstairs market.